Social Analysis of the Impact of Ethical Actions (Behaviors) on Social Progress from the Perspective of the Holy Book of Quran - Sayyid Ali Naqi Ayazi; Sayyid Mahmoud Marvian Hosseini (آموزه‌های قرآنی)
The ethical actions are important because of the priority of the mission goal and their close relationship with social progress and development. Therefore, the purpose of this research is the identification and social analysis of these types of actions among the verses of revelation and it deals with the effect of ethical actions in the production of social capital in the process of progress based on religious teachings and answers these questions based on the Quranic teachings. What impact do ethical actions (behavior) have on the formation of social progress? How do moral actions generate social capital and influence progress (development)? What coordinates, examples and dimensions does this group of actions have? What are the effects and consequences of this group of actions? Those actions that are desirable and progressive in the development of social interactions have been socially studied, analyzed and searched by using the inductive content analysis method. Honesty, trustworthiness and fulfillment of an obligation, altruism (Arabic: إیثار, self-sacrifice), asking forgiveness or istighfār (Arabic: استغفار ʾistiġfār), and forgiving others, kindness, non-violence, chastity and purity, patience and honesty and benevolent actions combined with social supervision have been discussed, which lead to sincerity, togetherness, coherence and expansion of social interactions and emotional relationships far from hatred and warm and emotional relationships and as a result, it causes the production of social capital and its improvement and will lead to the density of actions focused on purpose and excellence that are necessary for progress.